Drought index insurance policy subscription among cereal farmers in the Northern Region of Ghana - Boateng-Gyambiby Dominic (University of Cape Coast, 2019)
The study analyses the subscription to the drought index insurance policy among cereal farmers in the Northern Region of Ghana. The survey design and a choice experiment were used to elicit the hypothetical drought insurance policy preference for cereal farmers. A nluIti-stage sanlpling approach was used to randomly select 424 cereal farmers. Kendall's coefficient of concordance, Heckman's two-stage selection and Conditional logit model was used to analyse the data. The age of farmers.. farnl size, income, level of education and contact with an insurance extension agent statistically explained the determinants of insurance SUbscription whiles farming experience, farm size and off-farm income explained the intensity. Cereal farmers preferred a hypothetical drought index insurance policy with a premium of Gh(J:35 per acre, rainfall data from the Ghana Meteorological Agency weather stations, non-bank payment method for indemnity payout, credit interlinked with insurance, reduction of next season's premium when farmers do not experience loss and subsidy on the insurance prelnium. Farmers are willing to pay extra on the premium for an index insurance policy that is interlinked with credit, the next season's premium is reduced when loss does not occur and subsidized premium. In ranking constraints faced in subscribing to the insurance policy, the level of agreement between subscribers (11.1 %) was however slightly higher than non-subscribers (10.70/0). This suggests that the criteria used by subscribers for their ranking were relatively more homogenous as compared to the non-subscribers. The study suggests, among others the need for government to subsidize the premium on agricultural insurance.
xv,258p:,ill
Keywords: Subscription Drought Index Insurance Policy Cereal